Menggali Sifat Shidiq Amanah Fathanah Tabligh (SAFT) melalui Layanan Bimbingan Konseling Islami di SDIT Ar-Risalah Kartasura Tahun Ajaran 2016/ 2017 - Alhasan, Dian Na'imatul Fauzia; , Drs. Mulyadi, S. H., M. Pd (2017)
The objectives of this study are: 1) to describe Shidiq, Amanah, Fathanah, Tabligh (SAFT) found out in the islamic counseling service at SDIT Ar-Risalah Kartasura, 2) to describe islamic counseling service at SDIT Ar-Risalah Kartasura (Shidiq, Amanah, Fathanah, Tabligh) did have islamic counseling service that have Shidiq, Amanah, Fathanah, Tabligh (SAFT). This study employed qualitative research with phenomenology-based design. The subject of this study were the counseling teachers at SDIT Ar-Risalah Kartasura. The process of data collection involved several techniques which were: partisipative observation, interview, and documentation. The data were analyzed by reduction, display, dan verification with triangulation of sources and triangulation of methode as data validation technique. The findings of the study showed that: 1) this islamic counseling service have 4 positive character, Shidiq, Amanah, Fathanah, Tabligh, in their islamic counseling service 2) The teacher in-charge for each class played important role to provide the first counseling service, 3) Especially at the elementary level education, counseling service at school is the primary duty of the students' advisor, even though is fully handled by by the teacher in-charge for each class, 4)The counseling teacher majored in psychology in their bachelor degree is possible to be a students' advisor after joining uprading workshop. 5) SDIT Ar-Risalah Kartasura in provisioning SAFT characters applied some strategies: advising, exemplifying, customizing, and controling, 6) Supports from parents played important role in succeeding the process of provisioning SAFT characters in counseling and guidance.